Geophysical Studies In Setiu Lagoon-Estuary System - Yaakob, Rosnan (1988)
The study area is a shallow , bar-built , partially mixed lagoonestuary system , which undergoes changes in its pat tern of movement and mixing due to meteorological and river run-off changes. The Setiu estuary is of primary oceanographic interest since it is one of the large estuaries of the Terengganu coast into which two major rivers empty . A study of the system was conducted in 1985 and 1987 . Measurement s of the physical parameters were made monthly and during the anchored-stations period . More than 30 sediment samples were collected around the sampling stations. Temperature shows a seasonal variation isothermal at any single point in the system . and is generally Salinity variation is also seasonal and related to periods of high river discharge . Vertical stratification is present in the estuary but its intensity varies overtime with river discharge . The stratification is the result of salinity difference rather than variations in temperature . Salinity condition varies from near salt wedge to weak stratification near the estuary ' s inlet . Two major ' water masses ' are identified in the estuary area . Currents in the estuary area are due to river inf low and tides . The ebb flow is stronger than the flood due to the geographical and topographical nature of the system . These also control the circulation in the system. Surface wind stress also plays a role in setting up the flow pat tern . Most of the stronger winds occur during the North-east monsoon . This also influence sea waves and swell . The long-shore current is important in transporting sediment to the system. The sediment samples were mostly fine to very fine sands with mostly negative skewness . The estuary area is under the influence of transportative and erosive force . The lack of silt and clay in the estuary is attributable to less depositional factors under the influence of stronger current as compared to the lagoon area.